2021
DOI: 10.3390/molecules26133922
|View full text |Cite
|
Sign up to set email alerts
|

Size Effect of Graphene Quantum Dots on Photoluminescence

Abstract: High-photoluminescence (PL) graphene quantum dots (GQDs) were synthesized by a simple one-pot hydrothermal process, then separated by dialysis bags of different molecular weights. Four separated GQDs of varying sizes were obtained and displayed different PL intensities. With the decreasing size of separated GQDs, the intensity of the emission peak becomes much stronger. Finally, the GQDs of the smallest size revealed the most energetic PL intensity in four separated GQDs. The PL energy of all the separated GQD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 55 publications
0
20
0
Order By: Relevance
“…The PL of GO, GOQDs, and GQDs is affected by many factors, and the effective regulation of PL can be realized by clarifying its influencing factors. It is found that the influencing factors of PL include temperature, pH, size, elements, oxygen-containing functional groups, and some unconventional regulatory factors, according to previous studies [48][49][50][51]. The following will discuss the influencing factors on PL.…”
Section: Influence Factors and Regulation Of Luminescencementioning
confidence: 84%
See 2 more Smart Citations
“…The PL of GO, GOQDs, and GQDs is affected by many factors, and the effective regulation of PL can be realized by clarifying its influencing factors. It is found that the influencing factors of PL include temperature, pH, size, elements, oxygen-containing functional groups, and some unconventional regulatory factors, according to previous studies [48][49][50][51]. The following will discuss the influencing factors on PL.…”
Section: Influence Factors and Regulation Of Luminescencementioning
confidence: 84%
“…Obviously, appropriate size will be one of the factors affecting its PL, because size can change the sp 2 region, thereby changing the band gap. Li et al synthesized high PL GOQDs via a simple one-pot hydrothermal method, and then separated them with dialysis bags of different molecular weights to obtain four separated GOQDs with different sizes [ 50 ]. The study found that four separated quantum dots showed different PL intensities.…”
Section: Influence Factors and Regulation Of Luminescencementioning
confidence: 99%
See 1 more Smart Citation
“…The values of intensity ratio between the D and G bands (I D /I G ) indicate defects in graphene structures [ 112 , 114 , 117 , 152 , 157 ]. For example, in the Raman spectra of four GQDs separated using dialysis tubes filtering different molecular weights (1, 3.5, 7, and 14 kDa), I D /I G ratios for the different samples were 0.98, 0.93, 0.94, and 1, respectively ( Figure 5 f) [ 158 ].…”
Section: Characterizationsmentioning
confidence: 99%
“…( f ) Raman spectra of GQDs (1, 3.5, 7, 14 kDa), with detailed view of the D and G bands. Figure adapted from Reference [ 158 ]. Copyright 2021, MDPI AG.…”
Section: Characterizationsmentioning
confidence: 99%